Children and the media - Dennis, Everette E.; Pease, Edward C. (Transaction Publ., 1996)
I. Overview. Symposium I / Jana Eisenberg -- The moment of truth / Reed Hundt -- "As I told the FCC--" : yet another modest proposal for children's television / Peggy Charren -- Why kids hate educational TV / Patricia Aufderheide -- Electronic childhood / Ellen Wartella. II. Covering children. Symposium II / Jana Eisenberg -- From unseen and unheard to kidsbeat / Cathy Trost -- How the news media "see" kids / Dale Kunkel -- Children like me : where do we fit in? / Mar(c)Ưa Elena Guti(c)♭rrez. III. The child audience. Symposium III / Jana Eisenberg -- By the numbers : what kids watch / Larry McGill -- Six myths about television and children / Milton Chen -- "Ask Beth" / Elizabeth C. Winship -- "Sesame street" and children in poverty / Keith W. Mielke -- Teaching media literacy : yo! are you hip to this? / Ren(c)♭e Hobbs -- Growing media smarts : tne New Mexico project / Kate Moody. IV. Kids making media. Symposium IV / Jana Eisenberg -- A voice and the courage to use it / Robert Clampitt and Stephen Silha -- News advisory : listen to the children / Susan Herr and Dennis Sykes -- Our own voices, please / Marjani Coffey -- Harlem snapshot : schooling in new technologies / Josiah Brown -- Coming up next--a brighter tomorrow for kids' TV / Karen W. Jaffe. V. Books and organizations. Smarter than we think : kids, passivity and the media / Katharine E. Heintz -- The guardians of growing up : a user's guide to children and media research groups / Dirk Smillie